PENGARUH DEBT TO EQUITY RATIO, DIVIDEN PER SHARE, DIVIDEN PAYOUT RATIO, DAN NILAI TUKAR TERHADAP HARGA SAHAM PERUSAHAAN SEKTOR INFRASTRUKTUR YANG TERDAFTAR DI BEI TAHUN 2017-2021 - Muhammad Fathur Roziqin; Sjarief Hidajat (Jambura Economic Education Journal, 2023)
The research objective was to determine the effect of the Debt to Equity Ratio, Dividend Per Share, Dividend Payout Ratio, and the exchange rate on the stock prices of infrastructure sector companies listed on the IDX in 2017-2021. This research uses quantitative methods. The research population is all infrastructure sector companies listed on the IDX 2017-2022. The sampling technique used purposive sampling with a total sample of 11 companies selected. Analysis of research data using Partial Least Square (PLS) with the WarpPLS 8.0 version test tool. The result is that Debt to Equity Ratio is not significant to stock prices, Dividend Per Share is significant to stock prices, Dividend Payout Ratio and Value are not significant to stock prices. The research findings will become a new source of literacy for investors to be able to consider the factors that influence stock prices before investing in stocks so as to minimize investment losses.